Strategic planning and its role in crisis management. A case study of the Amal Institute for Orphans in the Gaza Strip - Hassan Diraoui, Aymen (Finance and Business Economies Review, 2020)
The research aimed to study the relationship between strategic planning and crisis management at the Amal Institute for Orphans in the Gaza Strip. The descriptive analytical method was used through the application of a comprehensive survey method for administrative leaders working in the Gaza Strip of (20) individuals. (18) questionnaires were retrieved with a response rate of (90%). Among the most important results presented by the research: There is a positive correlation between all dimensions of strategic planning (strategic vision ،strategic message ،strategic goals ،strategic analysis ،strategic choice) And crisis management at the Amal Institute for Orphans ،and the most important recommendations are: interest in strategic planning for its impact on Crisis management ،continuous training on strategic planning and crisis management ،especially young and ambitious cadres ،and assuming imaginary crises and their training in them ،adopted and developed independent administrative units concerned with strategic planning and crisis management.